Jenis dan Kelimpahan Relatif Lalat Buah Famili Lonchaeidae dan Tephritidae serta Parasitoidnya pada Cabai Rawit Putih (Capsicum frutescens L.) di Kabupaten Rembang, Provinsi Jawa Tengah, Indonesia - Ningtyas, Sinta Sulvia; Susila, I Wayan; Supartha, I Wayan (Agrotrop : Journal on Agriculture Science, 2023)
Types and Relative Abundance of Fruit Flies of the Lonchaeidae and Tephritidae Families and Their Parasitoids on White Cayenne Pepper ( Capsicum frutescens L.) in Rembang Regency, Central Java Province, Indonesia . Research on type and relative abundance of fruit flies Lonchaeidae and Tephritidae families and their parasitoids on white chili peppers ( Capsicum frutescent L.) in Rembang Regency, Central Java Province, aims to determine the types of fruit flies in the families Lochaeidae ( Bactrocera sp.) and Tephritidae ( Silba sp.) and parasitoids, abundance, and parasitization rate of fruit fly parasitoids. This research used a purposive method by taking 50 fruits that had symptoms of fruit fly attacks at each location point for 3 repetitions in Kaliori, Sluke, Pamotan, Sedan, and Bulu Districts. The research was conducted from November 2021 to March 2022. The results showed that the fruit fly species was Silba adipata from the Lonchaeidae family and Bactrocera dorsalis from the Tephritidae family. The relative abundance of the fruit fly S. adipata (38.49%) was lower than that of the fruit fly B. dorsalis (61.51%).  The fruit fly parasitoids of S. adipata are Asobara Japonica, Fopius arisanus and Diachasmimorpha longicaudata , and the fruit fly parasitoids of B. dorsalis are Fopius arisanus and Diachasmimorpha longicaudata . The average parasitization rate of the fruit fly parasitoid S. adipata was (27.13%) and B. dorsalis was (21.05%).